Discovery of a cyclotron absorption line in the transient X-ray pulsar XTEJ1829-098 - A. E. Shtykovsky; A. A. Lutovinov; S. S. Tsygankov; S. V. Molkov (OXFORD UNIV PRESS, 2022)
We report results of a spectral and timing analysis of the X-ray pulsar XTE J1829-098 using data obtained with the NuSTAR observatory during an outburst in 2018 August. A strong absorption feature was detected at the energy of E-cyc similar or equal to 15 keV in the source spectrum. This feature was interpreted as a cyclotron resonance scattering line corresponding to the magnetic field strength of the neutron star surface B similar or equal to 1.7 x 10(12) G. The pulse phase-resolved spectroscopy shows that the cyclotron line is significantly detected at all phases of the pulse and its energy and other parameters are variable over the pulse period. The timing analysis of the source emission revealed strong pulsations with a period of P = 7.84480(2) s. The pulsed fraction is changed with the energy, including its local increase in the vicinity of the cyclotron line. Using the archival data of the RXTE observatory the presence of the cyclotron line in the spectrum of XTE J1829-098 was independently confirmed and tentative hint for the possible anticorrelation of the line energy with the source flux was revealed.